Clonal analysis of B cells in the osteoarthritis synovium. Issue 8 (1st August 2001) - Shiokawa, S; Matsumoto, N; Nishimura, J
Abstract : OBJECTIVES: Cellular and humoral immunity to collagen and cartilage proteoglycan were shown in patients with osteoarthritis (OA). Inflammatory infiltration containing T and B lymphocytes and macrophages, which are HLA-DR positive, is often seen in the synovial membrane of patients with OA. An analysis of the DNA restriction enzyme patterns of T lymphocytes from the OA synovium showed an oligoclonal pattern of T cell receptor β chain gene rearrangements. No similar studies of B cell clonality have previously been performed. This study aimed at determining the clonal characteristics of the B cells in the OA synovium. METHODS: A reverse transcriptase-polymerase chain reaction of the immunoglobulin transcripts of B cells in the synovial membranes from six patients with OA was performed and the products were analysed by a single strand conformation polymorphism analysis. RESULTS: Several dominant bands were seen in all samples and some of the dominant bands were common among the two or three separate regions of each synovial sample. CONCLUSION: Infiltrated B cells are oligoclonal, and an antigen driven immune response may play a part in the progression of the disease process in OA.